Brainwashed challenging the myth of Black inferiority - Burrell, Tom. (Carlsbad Smiley Books, 2010)
?Black people are not dark-skinned white people,? says advertising visionary Tom Burrell. In fact, they are much more. They are survivors of the Middle Passage and centuries of humiliation and deprivation, who have excelled against the odds, constantly making a way out of ?No way!? At this pivotal point in history, the idea of black inferiority should have had a ?Going-Out-of-Business Sale.? After all, Barack Obama has reached America?s Promised Land.
"1st edition, February 2010; 3rd edition, March 2010"--T.p. verso.
Keywords: African Americans -Social conditions